Culture and Regional Language Based Tourism Economy: An Interdisciplinary Literature Review - Ahmad Turmuzi; Sofyan Hariono (Indonesian Journal of Education and Science, 2026)
This study is motivated by the limited systematic research on the integration of culture and regional language as core economic resources in tourism, despite their significant influence on destination competitiveness, sustainability, and cultural preservation. It aims to analyze the role of culture and regional language as symbolic and economic capital, identify dominant integration patterns in tourism development, and examine challenges and future directions of culture- and language-based tourism economies. The research employs a qualitative interdisciplinary literature review design, drawing on peer-reviewed journal articles and scholarly books published between 2015 and 2025, selected through purposive sampling. Data were collected through systematic document analysis and examined using thematic and comparative analysis to synthesize perspectives from tourism studies, cultural studies, linguistics, and the creative economy. Findings indicate that culture and regional language function as strategic symbolic assets that shape destination identity, strengthen perceptions of authenticity, and generate economic value when effectively mobilized within tourism systems, supporting cultural capital theory. Community-based tourism, participatory cultural governance, and linguistic landscape strategies emerge as the most effective integration patterns for achieving economic sustainability while safeguarding cultural integrity. However, persistent challenges—including over-commodification, cultural homogenization, unequal benefit distribution, and limited institutional capacity—remain significant barriers. The study concludes that integrating culture and regional language into tourism economies requires inclusive governance, ethical commodification, and innovation through digital storytelling and creative industries. The implications advance interdisciplinary tourism and cultural economy scholarship while informing policymakers and practitioners on sustainable, culture-based tourism strategies. Future research should employ empirical, comparative, and mixed-methods approaches across diverse regional contexts.